Perlindungan Hukum Merek Asing Terkenal Yang Bergantung Pada Sistem Konstitutif Di Indonesia - Muhammad Lukman Fadillah; Nahrowi Nahrowi; Ipah Farihah (Faculty of Sharia and Law State Islamic University Syarif Hidayatullah Jakarta, 2022)
In order to improve the similarity of peoples to perform passing off reputation on the other side, now, therefore, mark breaching is especially motivated by a desire to gain benefit in the goods and services trade with the other mark which has been famous or popular or with the passing off owner mark or well-known mark. Trading of the trademark in well-known mark speed on selling to the market will undoubtedly profit quickly. The behavior in violation of the law harmed a company's reputation. With regard to the